Exercise after You Eat: Hitting the Postprandial Glucose Target - Erickson, Melissa L.; Jenkins, Nathan T.; McCully, Kevin K. (Frontiers in Endocrinology, 2017)
We discuss a novel hypothesis: the effect size of postmeal exercise for attenuating postprandial glucose will be a function of the exercise bout vs. the size of the postprandial glucose response, specifically peak and duration of the postprandial glucose excursion.